Impact of corporate social responsibility, technological capability, and green entrepreneurial orientation on green innovation and sustainable performance - Jalal Rajeh Hanaysha; Mohammed Abusharbeh; Said Yousef Dwikat; Mohammad Fawzi Shubita; Muhammad Naeem Sharif; Sajead Mowafaq Alshdaifat (World Development Sustainability)
The primary purpose of this paper was to explore the effect of green entrepreneurial orientation, technological capability, and corporate social responsibility on sustainable performance and green innovation. It also aimed to verify if green innovation has any significant effect on the sustainable performance of small and medium enterprises. A quantitative research approach was utilized for data collection using a survey tool being distributed on several small and medium enterprises’ owners/managers in the United Arab Emirates. The samples SMEs are from services, manufacturing and trade industries. A total of 226 usable responses were obtained from all the respondents. The software of SmartPLS was employed to analyze the data and verify the hypotheses of this research. The findings confirmed that the effect of green innovation on sustainable performance is significant. Furthermore, the outcomes displayed that green entrepreneurial orientation, technological capability and corporate social responsibility positively affect green innovation and sustainable performance. Overall, the paper contributes to the literature via the examination of the predictors of sustainable performance and green innovation by bringing original insights from small and medium enterprises in the United Arab Emirates.